PENGARUH BUBUK BAWANG BOMBAI MERAH TERHADAP BIOMARKER INFLAMASI PADA MENCIT MODEL ARTHRITIS GOUT - Maulida Zaharani Victoriana; Luthfia Nabila; Diah Anggun Febriana Putri; Azizah Hikma Safitri; Nurina Tyagita (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2026)
Gouty arthritis is an inflammatory joint disorder caused by the accumulation of monosodium urate (MSU) crystals. It is characterized by elevated levels of several inflammatory biomarkers, including interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and C-reactive protein (CRP). Acute inflammation can be reduced by natural substances containing quercetin, which has anti-inflammatory properties, such as red onions (Allium cepa L.). This study aimed to determine the effect of red onion powder on inflammatory biomarkers in mice induced with MSU crystals. This study was conducted at the Food and Nutrition Study Center (PSPG) Laboratory, Gadjah Mada University (UGM), Yogyakarta, from July to August 2024. This true experimental study used a post-test control group design. Twenty-seven male Balb/C mice were divided into three groups: (1). control, (2). AG: mice induced with MSU crystals, and (3). ROP: mice induced with MSU crystals and treated with red onion powder. Gouty arthritis induction in the AG & ROP groups was performed using an intra-articular injection of MSU crystals at 1 mg/20 g BW, confirmed by the presence of plantar edema. The ROP group received red onion powder at a dose of 27 mg/20 g BW/day for seven consecutive days. IL-6, TNF-α, and CRP levels were measured using ELISA one day after treatment. Data were analyzed using one-way ANOVA with a significance level of 0.05. The mean of IL-6 (95.33±0.99 pg/mL), TNF-α (8.09±0.51 pg/mL), and CRP (0.93±0.01 ng/mL) levels in the ROP group were lower than those in the AG group (139.65±1.01 pg/mL; 16.07±0.27 pg/mL; 2.41±0.02 ng/mL) (p < 0.05). Administration of red onion powder affected inflammatory biomarkers in mice induced with MSU crystals. Keywords: gouty arthritis, inflammatory biomarkers, red onion powder DOI : 10.35990/mk.v9n1.p13-22